The Relationship of Hand Washing Behavior and the Incidence of Diarrhea among School-Age Children at SDN Citimun 1 Sumedang Regency in 2023 - Justian, Dini; Aji, Tri Waskito; Afriani, Dini (PHSAJ - Public Health Sebelas April Journal, 2024)
Clean and healthy living behavior is an approach that promotes healthy behaviors and preventive measures in maintaining children's health. One important aspect of clean and healthy living behavior is maintaining sanitary hygiene, including practices that can prevent diarrheal diseases. Diarrhea is a condition characterized by loose and frequent stools, which is usually caused by a digestive tract infection. The purpose of this study was to determine the relationship between clean and healthy living behavior of washing hands with the incidence of diarrhea in students at SDN Citimun 1 Sumedang Regency in 2023. The research method used is quantitative observational with a cross-sectional approach, which is an approach that is momentary at a time and not followed continuously over a period of time. The population in this study were third, fourth and fifth grade students of SDN Citimun 1, Cimalaka District, Sumedang Regency, totaling 91 students. The results showed a value of p=0.001, so there is a significant relationship between hand washing and the incidence of diarrhea. It is expected that students and other communities continue to maintain the health of the surrounding environment in preventing the incidence of diarrhea through good clean and healthy living behavior practices. And can educate and encourage people to follow steps that can help reduce the risk of diarrhea and other related diseases.